The Rio Tinto Aluminium way to project portfolio management : a look at how Rio Tinto Aluminium ISAL manages its project portfolio, key takeaways and drawbacks - Hákon Ólafsson 1974- (2016)
Project Portfolio Management (PPM) has grown in popularity in the recent decades. More and more companies have realized the benefits of PPM when it comes to selecting projects with limited resources and relevance to company strategy. Different portfolio management systems have been developed to fit the needs of different companies. One of those companies is Rio Tinto Aluminium (RTA). This paper studies the RTA PPM system that has been in development in recent years. The RTA PPM consists of two well know methods, strategic buckets and stage-gate. This paper will look at the literature available about these methods as well as scoring models and metrics used by RTA. Icelandic companies are still discovering portfolio management and there seems to be growing interests in Iceland. This paper may help other companies who are looking for ways to manage their portfolios. It should give the reader a good overview of how a large international company manages its portfolio and hopefully leave the reader with a greater understanding of portfolio management.